Teachers' Digital Literacy in Supporting the National Assessment and Deep Learning in Pesantren - Izzat Amini; Siti Mukassyifa (CV. Kalimasada Group, 2026)
This study analyzes the role of teachers' digital literacy in supporting the National Assessment and deep learning at TMI Al-Amien Prenduan, an Islamic boarding school (pesantren) that restricts the use of electronic devices in the classroom. A descriptive qualitative approach with a case study design was employed. Data were collected through semi-structured in-depth interviews, participant observation, and document analysis involving teachers, institutional leaders, and the Quality Assurance Agency responsible for educational quality management. Informants were selected purposively, and data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that teachers' digital literacy contributes most strongly during the lesson-preparation phase, when teachers use digital resources to enrich materials, master multiple references, and design effective teaching strategies. Digital literacy also supports deep learning by enabling teachers to present content in meaningful and contextual ways, and it strengthens institutional readiness for the National Assessment, particularly the Learning Environment Survey. The study concludes that in pesantren, digital literacy functions strategically as an indirect, behind-the-scenes support mechanism for learning and quality assurance without requiring intensive classroom technology use.